Ethics in Science : Ethical Misconduct in Scientific Research, Second Edition - D'Angelo, John G; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
Providing the tools necessary for a robust debate, this fully revised and updated second edition of Ethics in Science: Ethical Misconduct in Scientific Research explains various forms of scientific misconduct. The first part describes a variety of ethical violations, why they occur, how they are handled, and what can be done to prevent them along with a discussion of the peer-review process. The second presents real-life case studies that review the known facts, allowing readers to decide for themselves whether an ethical violation has occurred and if so, what should be done. With 4 new chapters and an updated selection of case studies, this text provides resources for guided discussion of topical controversies and how to prevent scientific misconduct. Key Features: Fully revised and updated text which explains the various forms of scientific misconduct. New chapters include hot topics such as Ethics of the Pharmaceutical Industry, The Responsibility of Science to the Environment and Summary of Ethics Guidelines of STEM Professional Societies. Provides the necessary tools to lead students in the discussion of topical controversies. Includes descriptions of real ethical case studies, a number of which are new for the Second Edition. This book is applicable to any science and any level of education.
Scientific misconduct in research: What is it, why does it happen, and how do we identify when it happens? -- What constitutes scientific misconduct? -- Authorship and intellectual property. -- Bad ethics vs. bad science. -- New results that prove old results wrong. -- The whistle-blowers dilemma. -- What are the penalties for scientific misconduct? -- Human and animal subjects. -- What is peer reviews role in scientific misconduct? -- Revisiting Vlad and Frankie. -- Can peer reviewers be unethical? -- What effect on the public does scientific misconduct have? -- MMR and autism. -- Climategate. -- HIV vaccine. -- Animal rights groups. -- Cold fusion. -- Bernard Kettlewell. -- Electromagnetic field and high-tension power lines. -- Fracking and pollution. -- What constitutes responsible conduct from the point+A76 of view of human and animal subjects in research? -- The ethics of the pharmaceutical industry. -- Science and the public. -- The role of government in scientific misconduct? -- The responsibility of science to the environment. -- Is there some research that shouldnt be done because of threats the results may pose to society? -- Summary of ethics guidelines of STEM professional societies. -- Can Scientific misconduct be prevented? -- Intentional negligence in acknowledgment of previous work. -- Deliberate fabrication of data. -- Deliberate omission of known data that doesnt agree with hypotheses. -- Passing another researchers data as ones own. -- Publication of results without consent of all the researchers. -- Failure to acknowledge all the researchers who performed the work. -- Conflict-of-interest issues. -- Repeated publication of too-similar results. -- Breach of confidentiality. -- Misrepresenting others work. -- Wrapping up. -- Case Studies. -- Darwin and Wallace. -- Rangaswamy SrinivasanVISX patent dispute. -- Schwartz and Mirkin. -- Corey and Woodward. -- Crdova, Scripps Research Institute, and Stockholm University. -- La Clair and hexacyclinol. -- Woodward and quinine. -- DNA. -- David Baltimore and Teresa Imanishi-Kari. -- John FennYale patent dispute. -- VIOXX. -- Index.
Includes bibliographical references and index.
Also available in print format.
Keywords: SCIENCE / Physics; TECHNOLOGY & ENGINEERING / Material Science; Case studies of scientific controversies; Ethical Misconduct in Scientific Research; Ethical violations; Ethics in Science; Failure to acknowledge researchers; science and ethics; scientific misconduct; Topical controversies; Research -- Moral and ethical aspects -- Case studies; Fraud in science -- Case studies; Electronic books